PERBEDAAN INTENSITAS PEMANFAATAN SUMBER BELAJAR TINGGI DENGAN RENDAH TERHADAP PRESTASI BELAJAR PROFESI KEGURUAN - Eka Khristiyanta Purnama; Istiyarti Istiyarti (Jurnal Kependidikan, 2014)
This research is aimed to examine the influence of high intensity and low intensity in using learning resources to students’ achievement. This is an ex post facto research with the population of 155 students in the Department of History, Faculty of Education, University of PGRI Yogyakarta. The sampling technique used in this research was cluster random sampling, by which 80 sample students were taken. Data were collected through two techniques, i.e. a questionnaire for collecting data on students’ intensity in using learning resources, and a test for collecting data on learning achievement of teaching profession. Data are statistically analyzed with analysis of variance (ANOVA). The research result point out that: there is a significant difference of students achievements of teacher profession subject between the students who have high and low intensity of learning resources usage (P = 0.011 < 0.05).